(untitled) (World Bulletin of Social Sciences, 2025)
Paralinguistic devices, encompassing gestures, facial expressions, tone modulation, and other nonverbal elements, are essential tools in modern communication. These devices complement verbal language by adding emotional depth, enhancing clarity, and fostering cultural understanding. This study explores the role of somatic-based paralinguistic elements in English and Uzbek, focusing on their linguistic, cultural, and functional dimensions. By analyzing idiomatic expressions, cultural practices, and the impact of digital technologies, the research highlights both universal patterns and unique cultural adaptations. The findings emphasize the necessity of integrating paralinguistic tools into educational and professional communication practices, as well as the transformative potential of these devices in bridging cross-cultural gaps.